DAMPAK PRESTASI KERJA, SENIORITAS, DAN LOYALITAS TERHADAP PROMOSI JABATAN (Studi Kasus Pada PT. BankBengkulu) - Tenti Suka Dewi; Sri Ekowati; Tezar Arianto (UM. Bengkulu, 2021)
The title of this research is the effect of job performance, seniority, and loyalty on promotion to the firefighting office and rescue Bengkulu city. Job promotion is the result of work in quality and quantity achieved by an employee in carrying out tasks in accordance with the responsibilities assigned to him. This study aims to determine the effect of work performance, seniority and loyalty on promotion to the firefighting office and rescue Bengkulu City. This research method is quantitative with a population of all employees of the Bengkulu city fire and rescue office, amounting to 57 people, while the sample was taken using a total sampling technique of 57 employees of the Bengkulu city fire and rescue office. Data collection techniques by means of observation and questionnaires.Data analysis techniques with multiple regression, test significance (t test) and (f test). The variables of this study are Job Performance (X1), Seniority (X2) loyalty (X3) Job promotion (Y).The place of this research is the Bengkulu City fire and rescue department, which is located at JL. Bhayangkara NO.47 KM 9 Bengkulu City. The results of this study are evidenced by the results of the t test showing the value of t_hit> t_ (Î± / 2) (3.3378> 2.0024) and (sig Î± = 0.001 <0.050). This means that H_0 is rejected and H_a is accepted. Work motivation has a significant effect on employee performance at the firefighting office and the rescue of the city of Bengkulu, this is evidenced by the results of the t test showing the value of t_hit> t_ (Î± / 2) (2.654> 2.0024) and (sig Î± = 0.009 <0.050). This means that H_0 is rejected and H_a is accepted. Job performance (X_1) seniority (X2) Loyalty (X3) together have a significant effect on promotion (Y) at the fire department and rescue city of Bengkulu, this is evidenced by the F test shows the value of F_count> F table, namely (28779> 1.8960) and (sig Î± = 0.000 <0.05). This means that H_0 is rejected and H_a is accepted.Â Keywords: Job Performance, Seniority, and Loyalty to Job Promotion